Efektifitas Manajemen Kelas Dalam Peningkatan Hasil Belajar Siswa - Evi Selva Nirwana (At-Ta'lim : Media Informasi Pendidikan Islam, 2014)
Improving student learning outcomes one with the support of effective classroommanagement. It is undeniable that the classroom teachers to create a safe and supportive arethe main factors that affect motivation, achievement, and student behavior. Good classroommanagement is not only indirectly to working with students in reducing deviant behavior andcan deal effectively when the behavior occurs, but also sustains a useful academic activities.So there are three areas of expertise needed by a teacher. The first; knowledge of how tomanage the classroom. second; subject matter knowledge (lessons). The third; understandingof the social background of students.